Reverberation from the Waves: To See with your Ear - Vasanthi Mariadass
The deep country of hearing, described in terms of geology more than in those of any other natural science, not only by virtue of the cartilaginous cavern that constitutes its organ, but also by virtue of the relationship that unites it to grottoes, to chasms, to all the pockets hollowed out of the terrestrial crust whose emptiness makes them into resonating drums for the slightest sounds